Elevated serum creatinine and low albumin are associated with poor outcomes in patients with liposarcoma. Issue 3 (8th September 2015) - Panotopoulos, Joannis; Posch, Florian; Funovics, Philipp T.; Willegger, Madeleine; Scharrer, Anke; Lamm, Wolfgang; Brodowicz, Thomas; Windhager, Reinhard; Ay, Cihan
ABSTRACT: Low serum albumin levels and impaired kidney function have been associated with decreased survival in patients with a variety of cancer types. In a retrospective cohort study, we analyzed 84 patients with liposarcoma treated at from May 1994 to October 2011. Uni‐ and multivariable Cox proportional hazard models and competing risk analyses were performed to evaluate the association between putative biomarkers with disease‐specific and overall survival. The median age of the study population was 51.7 (range 19.6–83.8) years. In multivariable analysis adjusted for AJCC tumor stage, serum creatinine was highly associated with disease‐specific survival (Subdistribution Hazard ratio (SHR) per 1 mg/dl increase = 2.94; 95%CI 1.39–6.23; p  = 0.005). High albumin was associated with improved overall and disease‐specific survival (Hazard Ratio (HR) per 10 units increase = 0.50; 95%CI 0.26–0.95; p  = 0.033 and SHR = 0.64; 95%CI 0.42–1.00; p  = 0.049). The serum albumin‐creatinine‐ratio emerged to be associated with both overall and disease‐specific survival after adjusting for AJCC tumor stage (HR = 0.95; 95%CI 0.92–0.99; p  = 0.011 and SHR = 0.96; 95%CI 0.93–0.99; p  = 0.08). Our study provides evidence for a tumor‐stage‐independent association between higher creatinine and lower albumin with worse disease‐specific survival. Low albumin and a high albumin‐creatinine‐ratio independently predict poor overall survival. Our work identified novel prognostic biomarkers for prognosis of patients with liposarcoma. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 34:533–538, 2016.